Assessment of Liver Fibrosis after Direct-Acting Antiviral Therapy in Compensated and Decompensated HCV-related Liver Disease - Mohammed, Mohammed Amin; Omar, Nesreen Moustafa (International Journal of Innovative Research in Medical Science, 2019)
Background and Aim: Successful HCV eradication was associated with significant improvement in liver histology. Direct-acting antiviral (DAAs) therapy is associated with a significantly higher rate of sustained virologic response (SVR) compared to interferon-based therapies. Several non-invasive methods have been developed and validated with robust reliability and clinical applicability. Although these non-invasive tests are valuable in evaluating hepatic fibrosis prior to HCV therapy, use of these measures in monitoring fibrosis regression after HCV eradication with DAAs is currently limited. So, the aim was to assess the impact of DAAs on fibrosis regression in chronic HCV Egyptian patients with either compensated or decompensated liver disease. Patients and Methods: A total of 228 Egyptian chronic HCV patients eligible for treatment with DAAs were enrolled in this prospective study. All subjects selected from outpatient's Hepatology clinic of Mansoura university hospital received DAAs with different regimens after consent. The endpoint was a sustained virologic response at 12 (SVR12) weeks post-treatment. All participants were evaluated non-invasively by fibrosis-4 index (FIB-4), Aspartate Aminotransferase-to-Platelet Ratio Index (APRI) score, and liver stiffness measurement (LSM) by fibroscan before DAAs treatment, at end of treatment (EOT), 6- and 12-months post-treatment. Results: SVR achieved by DAAs therapy was associated with significant improvement (p ˂0.05) of non-invasive fibrosis markers (FIB-4, APRI score, and LSM by fibroscan) from baseline compared to EOT, 6-and 12-months post-treatment among HCV patients with significant and advanced liver fibrosis. Conclusions: fibrosis regression after DAAs therapy regardless of fibrosis grade. Baseline LSM by fibroscan predicted fibrosis regression.